Current immunotherapy in rheumatoid arthritis. (September 2013) - Meier, Florian MP; Frerix, Marc; Hermann, Walter; Müller-Ladner, Ulf
Rheumatoid arthritis is a common autoimmune disease primarily manifesting as chronic synovitis, subsequently leading to a change in joint integrity. Progressive disability and systemic complications are strongly associated with a decreased quality of life. To maintain function and health in patients with rheumatoid arthritis, early, aggressive and guided immunosuppressive therapy is required to induce clinical remission. Antirheumatic drugs are capable of controlling synovial inflammation and are therefore named 'disease-modifying antirheumatic drugs' (DMARDs). This article aims to bridge the beginning of DMARD therapy with agents such as methotrexate, leflunomide, sulfasalazine, injectable gold and (hydroxy)chloroquine with biological therapies, and with the new era of kinase inhibitors. Mechanisms of action, as well as advantages and disadvantages of DMARDs, are discussed with respect to the current literature and current recommendations.